2020
DOI: 10.3897/mycokeys.66.49910
|View full text |Cite
|
Sign up to set email alerts
|

Hydnaceous fungi of China 8. Morphological and molecular identification of three new species of Sarcodon and a new record from southwest China

Abstract: Three new stipitate hydnoid fungi, Sarcodon coactus, S. grosselepidotus and S. lidongensis, are described and illustrated, based on morphological characteristics and nuc ITS rDNA + nuc LSU rDNA sequence analyses and a new record, S. leucopus, from China is reported. S. coactus is characterised by ellipsoid to round basidiocarps, reddish-brown to dark brown, felted pileal surface with white and incurved margins, simple-septate and partly short-celled generative hyphae and irregular subglobose, thin-walled, brow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Additionally, a distinct clade, “ Neosarcodon ”, was informally defined in the internal transcribed spacer (ITS) sequence analysis of that study. Mu et al ( 2021 ) also confirmed that the traditional concept of Sarcodon was not monophyletic, and their previously described new species of Sarcodon (Mu et al 2020 ) were shown to be nested in Hydnellum . Notably, all the known species in the traditional Sarcodon sect.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Additionally, a distinct clade, “ Neosarcodon ”, was informally defined in the internal transcribed spacer (ITS) sequence analysis of that study. Mu et al ( 2021 ) also confirmed that the traditional concept of Sarcodon was not monophyletic, and their previously described new species of Sarcodon (Mu et al 2020 ) were shown to be nested in Hydnellum . Notably, all the known species in the traditional Sarcodon sect.…”
Section: Introductionmentioning
confidence: 72%
“…ITS sequences of the specimens collected in China were almost identical to those of Larsson et al ( 2019 ). In Mu et al ( 2020 ), S. leucopus was documented as a new Chinese record based on molecular evidence, however, no pictures or descriptions based on the Chinese materials was provided. Mleczko et al ( 2011 ) has ever described this species in detail, and some descriptions in that study were different from the morphological characters observed in specimens collected from China.…”
Section: Taxonomymentioning
confidence: 99%
See 2 more Smart Citations
“…Specimens were deposited at the herbarium of the Institute of Applied Ecology, Chinese Academy of Sciences (IFP). Microscopic procedures followed Mu et al [38]. Structures were examined microscopically from sections mounted in Cotton Blue (CB): 0.1 mg aniline blue dissolved in 60 g pure lactic acid; CB+ = cyanophilous, CB− = acyanophilous.…”
Section: Morphological Studiesmentioning
confidence: 99%